Tasmanian Midlands: A case study of increasing sophistication in conservation planning and action over four decades. (30th December 2021) - Gilfedder, Louise; Appleby, Matt W.; Lechner, Alex M.; Sprod, Daniel; Carter, Oberon; Burgess, Sebastian; Davidson, Neil J.; Harris, Rowan
Summary: The conservation significance of the Tasmanian Midlands, an agricultural region that is largely privately owned and has suffered significant land degradation and loss of biodiversity, has been recognised since the 1980s. Four decades of conservation planning and implementation has seen the evolution of biodiversity protection, revegetation, bush rehabilitation and climate‐ready habitat restoration. Relationships and trust have been built enabling the development of capacity in the farming community and conservation sector. This paper presents for the first time the chronology of four decades of landscape conservation planning and implementation in the Tasmanian Midlands. Remnant protection, restoration and revegetation efforts have evolved from the site level to landscape scale, leading to a conservation approach incorporating ecological restoration in its broadest sense. Successive iterations saw key initiatives including Midlands Bushweb, Midlandscapes, the Midlands Conservation Fund and the Tasmanian Island Ark project. Spatial tools and models have grown from simple maps and aerial photos to early GIS products including farm plans (revolutionary in their day) and asset maps, to increasingly complex spatial models of corridors using least‐cost path analysis and fine‐scale multi‐species models of functional connectivity. However, critical to success in these challenging agricultural landscapes has been the relationships of trust and collaboration built between local farmers and conservation planners.